Mixed Phase Crystalline Hausmannite and Manganese Ferrite Nanoparticles with Magnetic Properties for Environmental Application. (2018) - Singh, N.H.; Bera, A.; Debnath, A.; Saha, B.
Abstract: High surface to volume ratio in ferrites results novel phenomena of nanomagnetism such as superparamagnetism, magnetic quantum tunneling and spin-glasslike behavior, attracting the science community. MnFe2 O4 is one of such important magnetic oxides with tunable magnetic properties and Mn3 O4 is the most stable form of manganese oxide with paramagnetic behavior. The composite of these two outstanding materials of is synthesized by a simple chemical precipitation method using NaOH as the precipitating agent. Ferric chloride anhydrous (FeCl3 ) and manganese chloride tetra hydrate (MnCl2 .4H2 O) were used as iron and manganese sources respectively. The samples were annealed at 400°C for eight hours to obtain homogeneous powder of Manganese ferrite. The powders were characterized by using X-ray diffraction (XRD), field emission scanning electron microscope (FESEM) and Fourier transform infrared spectroscopic (FTIR) measurements. The sample was found polycrystalline on X-ray diffraction study. The magnetic properties of the sample were investigated by vibrating sample magnetometer (VSM) measurements. From the magnetic moment vs. magnetic field plot, the sample was found to have high saturation magnetic moment of 30.12 emu/g. The synthesized nano-composite was used as adsorbent for removal toxic dye reactive orange (RO) from water and its easy magnetic serration process is explored. In addition to environmental application, this nano-composite with such an appreciable magnetic moment along with its electrical properties will be a candidate material for different applications in electronics and exploring its functionality in the field of recently developing semiconductor device physics and spintronics.